2021
DOI: 10.3390/app11135793
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Current in a Power Converter Using Fuzzy Automatic Gain Control

Abstract: The accuracy of current measurements can be increased by appropriate amplification of the signal to within the measurement range. Accurate current measurement is important for energy monitoring and in power converter control systems. Resistance and inductive current transducers are used to measure the major current in AC/DC power converters. The output value of the current transducer depends on the load motor, and changes across the whole measurement range. Modern current measurement circuits are equipped with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Many scientific papers have studied power converters, 122 which include different circuit topologies, soft switching control methods, and transformer optimization methods. However, the output powers of power converters in these scientific papers were not large, and there have been no in-depth studies on the input voltage range.…”
Section: Contributions Of Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scientific papers have studied power converters, 122 which include different circuit topologies, soft switching control methods, and transformer optimization methods. However, the output powers of power converters in these scientific papers were not large, and there have been no in-depth studies on the input voltage range.…”
Section: Contributions Of Previous Workmentioning
confidence: 99%
“…Both experimental and simulation results indicated that the power converter that used their proposed method had better robustness. Dominikowski 19 proposed a fuzzy gain system with high accuracy to improve the measurement accuracy of power converters. The simulation results showed that the fuzzy controller was feasible.…”
Section: Introductionmentioning
confidence: 99%